ABCs of the degenerative spine - Sergiy V. Kushchayev; Tetiana Glushko; Mohamed Jarraya; Karl H. Schuleri; Mark C. Preul; Michael L. Brooks; Oleg M. Teytelboym (Insights into Imaging, 2018)
Abstract Degenerative changes in the spine have high medical and socioeconomic significance. Imaging of the degenerative spine is a frequent challenge in radiology. The pathogenesis of this degenerative process represents a biomechanically related continuum of alterations, which can be identified with different imaging modalities. The aim of this article is to review radiological findings involving the intervertebral discs, end plates, bone marrow changes, facet joints and the spinal canal in relation to the pathogenesis of degenerative changes in the spine. Findings are described in association with the clinical symptoms they may cause, with a brief review of the possible treatment options. The article provides an illustrated review on the topic for radiology residents. Teaching Points • The adjacent vertebrae, intervertebral disc, ligaments and facet joints constitute a spinal unit. • Degenerative change is a response to insults, such as mechanical or metabolic injury. • Spine degeneration is a biomechanically related continuum of alterations evolving over time.